Effects of interleukin-1ß on cortical spreading depolarization and cerebral vasculature. Issue 5 (May 2017) - Richter, Frank; Eitner, Annett; Leuchtweis, Johannes; Bauer, Reinhard; Lehmenkühler, Alfred; Schaible, Hans-Georg
During brain damage and ischemia, the cytokine interleukin-1ß is rapidly upregulated due to activation of inflammasomes. We studied whether interleukin-1ß influences cortical spreading depolarization, and whether lipopolysaccharide, often used for microglial stimulation, influences cortical spreading depolarizations. In anaesthetized rats, cortical spreading depolarizations were elicited by microinjection of KCl. Interleukin-1ß, the IL-1 receptor 1 antagonist, the GABAA receptor blocker bicuculline, and lipopolysaccharide were administered either alone or combined (interleukin-1ß + IL-1 receptor 1 antagonist; interleukin-1ß + bicuculline; lipopolysaccharide + IL-1 receptor 1 antagonist) into a local cortical treatment area. Using microelectrodes, cortical spreading depolarizations were recorded in a non-treatment and in the treatment area. Plasma extravasation in cortical grey matter was assessed with Evans blue. Local application of interleukin-1ß reduced cortical spreading depolarization amplitudes in the treatment area, but not at a high dose. This reduction was prevented by IL-1 receptor 1 antagonist and by bicuculline. However, interleukin-1ß induced pronounced plasma extravasation independently on cortical spreading depolarizations. Application of lipopolysaccharide reduced cortical spreading depolarization amplitudes but prolonged their duration; EEG activity was still present. These effects were also blocked by IL-1 receptor 1 antagonist. Interleukin-1ß evokes changes of neuronal activity and of vascular functions. Thus, although the reduction of cortical spreading depolarization amplitudes at lower doses of interleukin-1ß may reduce deleterious effects of cortical spreading depolarizations, the sum of interleukin-1ß effects on excitability and on the vasculature rather promote brain damaging mechanisms.